2010
DOI: 10.1152/ajpheart.00607.2010
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular underfilling and not septal bulging dominates abnormal left ventricular filling hemodynamics in chronic thromboembolic pulmonary hypertension

Abstract: Chronic thromboembolic pulmonary hypertension (CTEPH) is associated with abnormal left ventricular (LV) filling hemodynamics [mitral early passive filling wave velocity/late active filling wave velocity (E/A) < 1]. Pulmonary endarterectomy (PEA) acutely reduces pulmonary vascular resistance, resulting in an increase of mitral E/A. The abolishment of leftward septal bulging and an increase in right ventricular (RV) output are thought to be responsible for the increase of mitral E/A. In this study, we quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Indeed, in this model, the first steps toward patient-specific modeling in PAH have led to a better understanding of left ventricular inflow patterns in PAH as well as to the interesting observation that right ventricular pacing in PAH might be beneficial [47, 48]. Computation times are limited thanks to the geometric simplicity of the model.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Indeed, in this model, the first steps toward patient-specific modeling in PAH have led to a better understanding of left ventricular inflow patterns in PAH as well as to the interesting observation that right ventricular pacing in PAH might be beneficial [47, 48]. Computation times are limited thanks to the geometric simplicity of the model.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The results suggested that that the abnormal E/A pattern was in large part due to decreased LV preload [6]. These findings were supported by Lumens et al using a computer-generated model that could separate the influences of septal bulging vs. LV filling on transmitral Doppler flow patterns pre- and post-PTE [7]. Gurudevan also reported that early diastolic mitral annular velocity (E’) was abnormally low in CTEPH but increased after PTE.…”
Section: Discussionmentioning
confidence: 81%
“…More recent studies, however, have supported the theory of decreased RV output and relative LV underfilling as the primary cause of the perceived LV diastolic impairment in CTEPH [5-7]. If this is correct, one might hypothesize that left atrial volume would increase after successful pulmonary thromboendarterectomy (PTE) and potentially correlate with improvements in right heart catheterization measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In the Windkessel model the circulatory system is a large compliant compartment (representing the major arteries) and a peripheral resistance (representing the capillaries) that opposes the blood flow. The arterial walls are considered rigid, and two parameters are not sufficient to account for high-frequency components of the pressure-volume relationship in non-rigid, compliant, wave propagating medium (Lumens et al, 2010; Stergiopulos et al, 1999). Therefore this model lacks the detail to generate realistic waveforms of the human circulatory system.…”
Section: Methodsmentioning
confidence: 99%